Optimalisasi LinkedIn sebagai Media Personal Branding untuk Meningkatkan Kesiapan Kerja Generasi Z - Ririn Uke Saraswati; Ranuyoga Arsyiandi; Suripto Moh. Zulkifli; Suci Damayanti; Aura Diva Maryam; Dwi Meilani Mulya Handayani P; Mita Puspita Sari; Siti Nurhalisa (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital era requires Generation Z to build a professional image early in order to compete in the job market. One effective strategy to support this need is developing personal branding through the LinkedIn platform. However, many students still lack understanding of how to create a professional LinkedIn profile. The seminar and training titled “The Importance of LinkedIn Profile as Personal Branding for Generation Z Entering the Workforce” was conducted at SMKS Dewantara to enhance students' knowledge and skills in optimizing their LinkedIn profiles. The training method included theoretical material, hands-on practice, discussions, and evaluation through pre-test and post-test instruments. A total of 30 students participated in this activity, and the evaluation results indicated a significant improvement in LinkedIn account ownership, understanding of personal branding, and ability to utilize LinkedIn features effectively. In addition, feedback from participants showed that the program was useful, relevant, and supported their preparation for future careers. Therefore, this training successfully increased students’ readiness to enter the professional environment by utilizing LinkedIn as a platform for strong personal branding.